The fantastic creatures of Bronze age Crete - Zouzoula, Evgenia (2007)
This thesis studies the imaginary beings of Minoan iconography with the aim of understanding their functions and meaning within the iconography of Bronze Age Crete. Two broad categories of Minoan fantastic creatures can be discerned, namely the imported and the locally created hybrids. With the exception of investigations of the genius, previous studies have focused mainly on matters of typology and style and, more importantly, have detached the illustrations of imaginary beings from their context of creation and use. Consequently, griffins and sphinxes are vaguely classified as "royal monsters", the dragon is merely considered as the transporter of deities, the reasons behind the creation of the bird-lady and the "Minotaur" are still unfathomable and the demonic creations of the Zakros workshop have not been explained at all and are simply viewed as meaningless. On the other hand, conjoined animals and less popular monsters, like the winged goats, have been more or less overlooked.